Interaction of the state and civil society institutions in the social sphere - Oleg Yastrebov, Aleksandr Polukarov,; Akimzhanov, Talgat; Kutuyev, Adam (Opción, 2019)
This article is aimed at developing the forms and methods of interaction of the state and civil society institutions in the direction of anti-corruption in the social sphere via formal-legal and comparative-legal methods. The results of the work are the disclosure of the essence of forms of interaction of the state and civil society institutions in the system of anti-corruption, determination of types of means, used in the mechanism of anti-corruption in the social sphere. In conclusion, an important aspect of the effective work of civil society institutions in anti-corruption in the social sphere is their economic independence and professionalism.